Sleep Disorders among Employees in the Evening Shift in the Hospital: A Systematic Review (The International Journal for Scientific Research, 2023)
Introduction: Sleep disturbances are prevalent among nurses, so they are exposed to adverse negative consequences, affecting their health, and subsequently affecting the quality of the provided nursing care, and overall, the performance and productivity.  Methods: An electronic search in PubMed and Embrace was conducted to identify eligible articles. After exclusion of ineligible and duplicated articles, 52 articles were included in this review.Results: The findings of this review revealed that working in night shifts, physiological status of nurses, and demographic variables, such as age, sex, nutritional habits, and Energy Drinks of hospital nurses, and the period of the COVID-19 pandemic are influencing factors affecting the quality of nurses’ sleep. The negative consequences of poor sleep include disturbance in cognitive and behavioral functions, the risk for injuries and infections, low quality of nursing care, errors, and mistakes.Conclusions: There are several solutions that could be implemented to manage the situation, instrumental, or on self-adjustment, avoidant, task oriented and emotion oriented. The nurses should be provided with coping mechanisms to engage in quality of sleep and minimize the negative consequences of poor sleep associated with the nature of their work. The approved interventions used to enhance sleepiness among nurses include bright lighting exposure, napping, rescheduling of shift work and behavioural changes.
Keywords: Sleep; Disturbances; Problems; Nurses; Occupational Health